High-energy terahertz surface optical rectification. (April 2018) - Peters, L.; Tunesi, J.; Pasquazi, A.; Peccianti, M.
Abstract: The interest in surface terahertz emitters lies in their extremely thin active region, typically hundreds of atomic layers, and the agile surface scalability. The ultimate limit in the achievable emission is determined by the saturation of the several different mechanisms concurring to the THz frequency conversion. Although there is a very prolific debate about the contribution of each process, surface optical rectification has been highlighted as the dominant process at high excitation, but the effective limits in the conversion are largely unknown. The current state of the art suggests that in field-induced optical rectification a maximum limit of the emission may exist and it is ruled by the photocarrier induced neutralisation of the medium's surface field. This would represent the most important impediment to the application of surface optical rectification in high-energy THz emitters. We experimentally unveil novel physical insights in the THz conversion at high excitation energies mediated by the ultrafast surface optical rectification process. The main finding is that the expected total saturation of the Terahertz emission vs pump energy does not actually occur. At high energy, the surface field region contracts towards the surface. We argue that this mechanism weakens the main saturation process, re-establishing a clearly observable quadratic dependence between the emitted THz energy and the excitation. This is relevant in enabling access to intense generation at high fluences. Graphical abstract: fx1 Highlights: Novel insight into high-energy terahertz emission mechanism from surfaces. Understanding the limit of surface terahertz emission. THz governed by "optical"-doping.